PENGARUH KONSENTRASI ETANOL TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN RAMBUSA (Passiflora foetida L.) MENGGUNAKAN METODE ULTRASONIC ASSISTED EXTRACTION (UAE) - Ananta Divasti Guna, I Made; Kencana Putra, I Nengah; Sri Wiadnyani, AA. (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i03.p05, 2020)
This study was conducted to determine the effect of ethanol concentration on antioxidant activity and to obtain the highest antioxidant activity in rambusa leaves extract using the UAE method. The experimental design used in this study was a completely randomized design (CRD) with an ethanol concentration treatment consisting of five levels, namely 50%, 60%, 70%, 80%, and 90%. All treatments were repeated three times to obtain 15 experimental units. The data obtained were analyzed by the analysis of variance (ANOVA) and if the treatment had a significant effect, then followed by the Duncan test. The results showed that ethanol concentration had a significant effect on yield, total phenol, total flavonoids, total tannins, and antioxidant activity. The results showed that the treatment of 70% ethanol concentration was the best. The treatment produced the extract with a yield of 25,14%, total phenol of 40,94 mg GAE/g extract, total flavonoids of 38,95 mg QE/g, total tannin of 33,49 mg TAE/g, the antioxidant activity based on free radical inhibition percentage of 70,58 %, and IC50 values of 328.20 mg/L.